Light Reflection Function for Simulation of Clouds and Dusty Surfaces - Blinn, Jim (Siggraph 1982, 1982)
The study of the physical process of light interacting with matter is an important part of computer image synthesis since it forms the basis for calculations of intensities in the picture. The simpler models used in the past are being augmented by more complex models gleaned from the physics literature. This paper is another step in the direction of assimilating such knowledge. It concerns the statistical simulation of light passing through and being reflected by clouds of similar small particles. (It does not, however, address the cloud structure modeling problem). By extension it can be applied to surfaces completely covered by dust and is therefore a physical basis for various theories of diffuse reflection.